Strength training recommendations to improve scrum force and impulse in Rugby Union forwards - Mills, B. S.; McMaster, D. T.; Smith, B. (Strength and Conditioning Journal, 2019)
Optimal scrum performance in rugby union requires the forward pack to produce a large sustained coordinated horizontal impulse. Training horizontal impulse and force for scrummaging is not easily simulated with traditional resistance training exercises (e.g., squat, deadlift, and clean). Therefore, it is proposed that the inclusion of heavy horizontally resisted exercises (e.g., sled push and scrum machine) within a given training phase be included to provide a greater transfer of force to the rugby scrum. This article (a) provides an overview of the physical demands and biomechanics of scrummaging, and (b) provides strength training guidelines to improve scrummaging force production.